Spatial Memory and Ecologically Displaced Subjectivity in Western Tharu Folk Songs of Nepal - Dangaura, Mohan (Literary Studies, 2022)
This paper critically examines the folk dance songs of Dangaura Tharu fromthe perspective of space, memory, and performance. The paper establishes the relationship between Tharu subjectivity and conscience of their past topography inherent intheir folk dance songs. In one aspect where the overall folk performance of Tharu reflects their lifestyle, in another aspect, their folk songs and rituals assist them to connect with the natural environment where they inhabit. This paper has brandied their performance as the art reflecting their bucolic lifestyle and melancholic memory. The songs have been collected, translated, and interpreted from different visual sources and personal communications. To analyze the primary texts, the notion of folklore performance from Alan Dundes, Richard Schechner, and other different folklorists have been utilized as the theoretical and review guidelines. The paper also includes the translated version of the songs. As for the indigenous culture aspirant like me, the study of folklores of Tharu indigeneity helps us to understand the spatial memory of one of the largest ethnicity of Nepal and their socio-economic history. It will provide a new perspective of their historical changes from literature which have not been critically assessed in the already conducted studies. Hence, the findings of the research help us to understand the necessary social index of one of Nepal’s largest indigeneity.